Education of Diabetic Medication for Type 2 Diabetes Mellitus Patients and Their Families in Ledokombo Village, Jember Regency: Edukasi kepada Keluarga dan Penderita Diabetes Melitus Tipe 2 tentang Cara Penggunaan Obat di Desa Ledokombo, Kabupaten Jember - Agnis Pondineka Ria Aditama; Dyan Maulani; Luthfiyah Nafisah; Anggraini Puspitasari; Dimas Agung Abdurrahman Wahid; Alfi Nur Ramadhani (KHD Production, 2024)
Diabetes Mellitus (DM) is a disease characterized by an abnormal increase in blood sugar levels. The most frequently encountered type of DM is Diabetes Mellitus type 2. Type 2 DM is a condition that lasts a lifetime, so it has an impact on reducing the quality of human life. This happens because the body cannot produce and use insulin effectively so that sugar levels continue to increase. Type 2 DM is experienced by several people in Ledokombo Village, Jember Regency. Type 2 DM sufferers need to change their behavior, namely their eating patterns, taking medication and regular check-ups to manage their disease. The aim of this activity is to increase knowledge about how to use type 2 DM medication among the community in Ledokombo Village, Jember Regency. The method used is to provide education to families or type 2 DM sufferers about how to use the drug. The results of the activity show an increase in public knowledge and understanding of how to use type 2 DM medication. Knowledge before being given education shows the lowest value of 17.39% and the highest 100%, while after being given education shows the lowest value of 43.48% and the highest 100%. Increased public knowledge about how to using type 2 DM medication can provide motivation for healthy living to manage the disease.